The microstructure and mechanical properties evaluation of UFG Titanium Grade 4 in relation to the technological aspects of the CONFORM SPD process. (2017) - Palán, Jan; Procházka, Radek; Zemko, Michal
Abstract: Processes based on severe plastic deformation (SPD) that are capable of producing microstructures with sizes on the order of nanometres are gaining importance these days. Their typical limitation is the small volume of the material processed. One of available ways to enhancing the productivity is to combine the CONFORM continuous extrusion process with the ECAP method. In the present study, commercially pure Grade 4 titanium was processed using the CONFORM SPD machine. The process was carried out at 220 °C. In total, three passes through the CONFORM SPD equipment were completed. The first pass through the CONFORM SPD machine led to a considerable reduction in grain size: from 12500 nm to 300–400 nm. Subsequent passes did not refine the grain any further. Instead, equiaxed grains were obtained. The mean grain size even increased after the third pass to values in the range of 400–450 nm. The first pass resulted in a marked increase in ultimate strength from 650 MPa to 750 MPa. Subsequent passes led to smaller increments that corresponded with the grain sizes attained. After the third pass, the ultimate strength reached 773 MPa. The present study highlights the potential of the continuous production of UFG materials by application of large deformation, and describes the dependence of materials characteristics on technological aspects of the process.